The synthesis approach to analysing educational design dataset: Application of three scaffolds to a learning by design task for postgraduate education students. (September 2015) - Thompson, Kate; Carvalho, Lucila; Aditomo, Anindito; Dimitriadis, Yannis; Dyke, Gregory; Evans, Michael A.; Khosronejad, Maryam; Martinez‐Maldonado, Roberto; Reimann, Peter; Wardak, Dewa
Abstract The aims of the Synthesis and Scaffolding Project were to understand: the role of specific scaffolds in relation to the activity of learners, and the activity of learners during a collaborative design task from multiple perspectives, through the collection and analysis of multiple streams of data and the adoption of a synthesis approach to the research. The Synthesis Approach to Analysing Educational Design (SAAED) dataset is comprised of video, audio and image files, transcripts of the discourse, as well as copies of physical artefacts generated by three groups of three postgraduate education students during a 90‐minute design session. The data were collected in January 2013. Each group was given a different scaffold related to the design process, the social interactions or the use of the tools available to the participants. Researchers interested in analysing the SAAED are required to sign a collaborator agreement to become part of the project team.